Politics of Sharia Banking Law in Indonesia - Muhammad Tun Samudra (IHSA Institute, 2022)
Basically, Islamic banks have the same function as conventional banks, namely as intermediate institutions that carry out their functions by collecting funds from the public, managing them, then channeling them back to people in need in the form of loans, but of course the government will not establish Islamic bank institutions if basically their functions are will be the same as conventional banks. The purpose of this study was to determine the role of legal politics on the development of Islamic banking in Indonesia. This research was structured using descriptive analysis method using a form of library research, with a detailed description of the existing facts, both in the form of secondary data, primary legal materials, and tertiary legal materials. Based on the research findings, it can be concluded that the development of Islamic banking. This can be proven by the gradual start of sharia banking regulations from when it was still a profit-sharing bank in Law Number 7 of 1992. This was further strengthened in Law Number 10 of 1998 with the term bank operating according to sharia principles. Until finally confirmed independently in Law No. 21 of 2008